2014
DOI: 10.1080/00103624.2013.867054
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol Application Alleviates Boron Toxicity in Wheat Seedlings

Abstract: Boron (B) toxicity is a considerable mineral nutritional problem for crop production in arid and semi-arid regions worldwide. The effect of mannitol (M) in wheat seedlings that are tolerant and sensitive to excessive B was studied to reduce B toxicity symptoms. Plants were grown in a peat with different concentrations of boric acid (0, 30, 45, 60 mg kg −1 ) and treated additionally with M (0, 1, 5, 10 g kg −1 ). Seedlings grown for 8 weeks were harvested for root length, shoot length, and dry-weight measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, in our study, despite having a general detrimental effect on the SL of the studied accessions, a very few accessions (Ab2, Ac4, and Al1) could tolerate the highly toxic B supply and showed a significant increase in SL (Figure 3B). Though a few studies reported no effect of B toxicity on SL (Yau and Saxena, 1997;Brdar-Jokanovic, 2020), others reported a significant negative effect of high B on the SL of wheat cultivars (Coskun et al, 2014). These differences in the results of the RL and SL direct toward a major role of genotypic variation in response to B toxicity.…”
Section: Impact Of B Toxicity Stress On the Root-shoot Growth Parametersmentioning
confidence: 95%
“…However, in our study, despite having a general detrimental effect on the SL of the studied accessions, a very few accessions (Ab2, Ac4, and Al1) could tolerate the highly toxic B supply and showed a significant increase in SL (Figure 3B). Though a few studies reported no effect of B toxicity on SL (Yau and Saxena, 1997;Brdar-Jokanovic, 2020), others reported a significant negative effect of high B on the SL of wheat cultivars (Coskun et al, 2014). These differences in the results of the RL and SL direct toward a major role of genotypic variation in response to B toxicity.…”
Section: Impact Of B Toxicity Stress On the Root-shoot Growth Parametersmentioning
confidence: 95%
“…However, 0.25 mM B treatment seemed to alleviate the reductions in root and shoot FW, shoot DW, root and shoot lengths resulted from drought stress by causing 42, 17, 26, 33 and 14 % increases, respectively, in comparison to 0.05 mM B treatment (control) plants. Growth reduction resulting from B toxicity has also been reported in barley (Karabal et al, 2003), tomato (Cervilla et al, 2007; and wheat (Coskun et al, 2014).…”
Section: Resultsmentioning
confidence: 88%
“…For the determination of SWC, whole germinated seedlings were weighed before and after drying at 70°C for 24 h (Coskun et al., 2014; Ge et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…For each treatment, GP, SVI, and SWC were calculated as follows: (Ali & Idris et al, 2015;Caruso et al, 2018;Ilori et al, 2012) Seeds were counted as normally germinated when the radicle extrusion was at least 3 mm (Almaghrabi, 2012). (Ali & Idris et al, 2015;Caruso et al, 2018) (Ge et al, 2016) For the determination of SWC, whole germinated seedlings were weighed before and after drying at 70°C for 24 h (Coskun et al, 2014;Ge et al, 2016).…”
Section: Germination and Seedlings Growth Parametersmentioning
confidence: 99%